Investigation on creep age forming of AA2219 stiffened structures - Yang Haoliang; Liu Lidong; Chen Haipeng; Wang Liliang; Qin Tong (MATEC Web of Conferences, 2015)
The research described in this paper is a study of CAF a 2219 aluminium alloy, which is used for fabricating the isogrid structure for fuel tanks of launch vehicles. The main aim of the research is to develop a small scale CAF test rig, which was designed to analyse the springback behaviour from CAF. The main objective of the experiment was to investigate the potential proposals of creep age forming stiffened structures. Based on the results of the experiment, a potential CAF process for forming 1/3 pieces of an isogrid cylindrical assembly was proposed.